Comparative Efficacy Analysis of Intubation Profile in Airtraq Video Laryngoscope Versus Macintosh Laryngoscope in Simulated Difficult Airway Using Cervical Collar (Indian Journal of Forensic Medicine & Toxicology, 2022)
Aim: Comparative efficacy analysis of laryngoscopes -Airtraq vs macintosh - using Intubation Time and Intubationdifficulty score in simulated difficult airway using cervical collar.Methods: Peculiarity is simulated difficult airway by use of cervical collar. A prospective interventionalrandomizedstudy conducted on 60 adult ASA grade-I&II patients scheduled for surgery in tertiary care center.Tracheal Intubation 1. Group(AVL) Airtraq videolaryngoscope (n=30) 2. Group(ML) Macintoshlaryngoscope(n=30). Parameters observed: 1) Intubation Time- seconds 2) Intubation Difficulty Score (IDS) comprised Numbersof-1. intubation attempts 2.operators 3.alternative intubation techniques, 4. Glottic exposure. 5. paramatriccomparison lifting force required during laryngoscopy, Necessity for external laryngeal pressure, Position of thevocal cords.Results: With airtraq laryngoscope intubation discoursed outcomes intubation time is irrelevant with difficultairway where it is highly associated in case of macintosh laryngoscope. Intubation time & difficulty score iscommentating use of Airtraq laryngoscope.Conclusions: The enhanced visual interiors expedite in such a way that intubation time in Airtraq is not dependenton IDS like Macintosh but on neuromuscular reflexes of performer, commentating the superiority of Airtraq overMacintosh
Keywords: airway, intubation, cervical collar, Airtraq, Macnitos, Laryngoscope